Journal of Labor Economics - Society of Labor Economists (Chicago University of Chicago Press, 1996)
The Journal of Labor Economics (JOLE) presents international research on issues affecting social and private behavior, and the economy. JOLE’s contributors investigate various aspects of labor economics, including supply and demand of labor services, personnel economics, distribution of income, unions and collective bargaining, applied and policy issues in labor economics, and labor markets and demographics.
​JOLE is the official journal of the Society of Labor Economists Published 4 issues/year (January, April, July and October). Some no. issued in two parts, pt. 2 being a special issue with distinctive title and separate paging from the rest of the vol. Full text articles availble on JSTOR
Keywords: Labour economics; LABOUR ECONOMICS; LABOUR; ECONOMIC RESEARCH